2015
DOI: 10.1111/cdep.12132
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Read Chinese: Universal and Unique Cognitive Cores

Abstract: How do children learn to read Chinese? Three abilities identified as cognitive cores for reading in alphabetic orthographies are letter knowledge, phonemic awareness, and rapid automatized naming (RAN;Hulme & Snowling, 2013). What are the cognitive cores for Chinese? Identifying such cores is important for two reasons. First, if they can be identified, cores can be tested early to distinguish those children who might be at risk for reading difficulties, helping prevent and remediate dyslexia. Second, training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Consequently, the present findings may be explained by two possible underlying mechanisms—on the one hand, more precise ANS representations may enable Chinese children to develop more elaborate counting skills than their German peers. More precise ANS representations of Chinese children might be traced back to more sophisticated visual-spatial skills (Zhou et al., 2015; see also Lonnemann et al., 2019), which have been observed as early as in preschool age and which are assumed to be a consequence of learning to read Chinese characters (see McBride-Chang et al., 2011; McBride and Wang, 2015). In this regard, it has been suggested that performance in visually presented non-symbolic numerical magnitude comparison tasks depends on the ability to integrate different visual cues (Gebuis et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the present findings may be explained by two possible underlying mechanisms—on the one hand, more precise ANS representations may enable Chinese children to develop more elaborate counting skills than their German peers. More precise ANS representations of Chinese children might be traced back to more sophisticated visual-spatial skills (Zhou et al., 2015; see also Lonnemann et al., 2019), which have been observed as early as in preschool age and which are assumed to be a consequence of learning to read Chinese characters (see McBride-Chang et al., 2011; McBride and Wang, 2015). In this regard, it has been suggested that performance in visually presented non-symbolic numerical magnitude comparison tasks depends on the ability to integrate different visual cues (Gebuis et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They were also assessed on the Chinese version of the combined Raven’s Progressive Matrices test (Zhang & Wang, 1985), obtaining a standardized score equal to or above 80; two poor readers were excluded from the initial sample of 24 participants, due to a score below 80. Moreover, they were tested for phonological awareness and morphological awareness, which have been claimed to be essential for learning Chinese (McBride & Wang, 2015). Phonological awareness was assessed with onset detection, rhyme detection and tone detection tests, and morphological awareness was assessed with homophone awareness and homograph awareness tests (Hu et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Another explanation emphasizes that both common and specific skills may underlie learning to read different orthographies (Geva & Siegel, ; McBride & Wang, ; Shum, Ho, Siegel, & Au, ; M. Wang, Koda, & Perfetti, ). For example, although phonological awareness, phonological memory, and rapid naming may be universally important for learning to read any orthography (Caravolas et al., ; Ziegler et al., ), the associations between reading and subcomponents of phonological awareness may vary across orthographies (for a review, see Ziegler & Goswami, ).…”
Section: The Relation Between Native‐ and Second‐language Reading Difmentioning
confidence: 99%